Risk Factors of Ovarian Cancer in PKU Muhammadiyah Teaching Hospital Yogyakarta - Wenang, Supriyatiningsih; AN, Alfun Dhiya; Pratiwi, Witri Andi; Lelle, Ralph J.; Haier, Joerg (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2020)
Introduction: Ovarian cancer is non-communicable diseases that has a high mortality rate. In PKU Muhammadiyah Teaching Hospital Yogyakarta in 2014-2017, ovarian cancer is 5th out of all types cancers diagnosed. Most of them are asymptomatic in early stage and come to hospital at late stage. Recognize and identify the risk factors of ovarian cancer are very important to prevent the patient from morbidity and mortality. The purpose of this study was to know the relationship between low parity, infertility, age, and family history with ovarian cancer in PKU Muhammadiyah Teaching Â Hospital Yogyakarta.Methods: This study was an observational analytical study with cross sectional design. The sample was medical record of women with ovarian cancer and non ovarian cancer in PKU Muhammadiyah Teaching Hospital Yogyakarta period of April 2014-September 2017 with inclusion and exclusion criteria. Data analysis used chi-square test.Result: The bivariat analysis showed that there is no relationship between low parity with ovarian cancer (p=0,790 OR=0,87; 95% CI 0,305-2,466), there is no relation between infertility with ovarian cancer (p=0,104 OR=2,48; 95% CI 0,815-7,545), and there is no relation between family history with ovarian cancer (p=0,304 OR=3,18; 95% CI 0,315-32,039). But there is a relationship between age with ovarian cancer (p=0,01 OR=0,11; 95% CI 0,022-0,510).Conclusion: There are no relations between low parity, infertility, and family history with ovarian cancer. But there is a relationship between age with ovarian cancer.